Microstructural and Mechanical Characterization of Corroded Aluminum Wires from ACSR Strand - Laurent Gaillet; Alan Rondineau; Sébastien Langlois; Marc Demers; Lamine Dieng (Corrosion and Materials Degradation, 2025)
Aluminum Conductors Steel-Reinforced (ACSR) conductors are typically used in overhead transmission lines. Corrosion is an important degradation mechanisms that might affect the lifetime of this essential electricity network component. Considering the complexity of conductors, it is difficult to predict the damage of these conductors in corrosive environments. The objective of this paper is to evaluate the effect of grease and conductor geometry on the mechanical properties of aluminum strand composing the envelope of ASCR conductors. Thus, ACSR wires and strands have been evaluated in corrosion by the mean of accelerated corrosion tests. Tensile, fatigue and torsion test results are presented to examine the effect of corrosion on aluminum strands. The influence of corrosion on mechanical characteristics is established by a decrease in ductility, maximum elongation and tensile strength for the longest exposition (336 days). This significant reduction in the internal layer of ungreased wires confirms the importance of the galvanic corrosion mechanism of aluminum wires. This evolution concerns only aluminum wires of non-greased conductors, confirming the crucial role of grease as protection against corrosion.